Monophosphoryl lipid A enhances both humoral and cell-mediated immune responses to DNA vaccination against human immunodeficiency virus type 1. - Sasaki, S (1997)
To enhance immunity induced by DNA vaccination against human immunodeficiency virus type 1 (HIV-1), we evaluated the efficacy of monophosphoryl lipid A (MPL), an adjuvant of bacterial origin. BALB/c mice were intramuscularly injected with immunogenic DNA, encoding the env and rev genes of the HIV-1(IIIB) strain, formulated with MPL dissolved in different vehicles (MPL in stable emulsion and MPL in aqueous formulation). The sera from mice immunized with the two preparations of MPL revealed 2(6) to 2(9) times higher HIV-1-specific immunoglobulin G (IgG) titers than the sera from mice immunized without MPL. In virus neutralization tests for HIV-1(IIIB), by p24 assay and antifusion assay of infected MOLT-4 cells, MPL tends to elicit antibody more protective than antibody elicited without adjuvant. MPL also elicited stronger delayed-type hypersensitivity and cytotoxic-T-lymphocyte activity against HIV-1(IIIB) compared to DNA alone. HIV-1-specific IgG subclass analysis showed that MPL tends to facilitate IgG2a production, suggesting enhancement of a predominant T-helper-type-1 response, and this enhancement may help to facilitate protective-antibody induction. Furthermore, a chloramphenicol acetyltransferase (CAT) assay was employed to determine whether MPL affected the gene expression process. Interestingly, both MPL preparations reduced CAT activity in the muscle injected with CAT expression vector but increased anti-CAT antibody production. These results indicate that MPL acts as an effective adjuvant for immunogenic DNA injection despite reduced expression of encoding protein in muscle. We conclude that MPL has a strong adjuvant effect on DNA vaccination against HIV-1.